"Dancing Backward in High Heels": Examining and Addressing the Disparate Treatment of Energy Efficiency and Renewable Resources - Scott,Inara (Environmental Law, 2013)
Both energy efficiency and renewable resources offer significant benefits to utilities, their customers, and society as a whole. Yet energy efficiency programs face formidable barriers to adoption that renewable resources do not. While both renewable and efficiency resources have received significant funding in recent years, government support for renewables continues to dwarf that for efficiency measures, and regulatory policies consistently discourage utilities from investing in efficiency measures even while they incentivize investment in renewables. This Article examines the parallel development of renewable resource and energy efficiency programs within utilities, compares the differing treatment of each, and offers concrete recommendations for enhancing energy efficiency adoption by modifying existing policies to more closely resemble those applied to renewable resources. The Article concludes that the historic disincentives to implementing efficiency policies can be remedied by: 1) updating ratemaking structures to ensure utilities can recover and earn on efficiency investments; 2) streamlining cost effectiveness tests that presently encourage utilities to underestimate and under-invest in efficiency programs; and 3) addressing market barriers by strengthening consumer incentives and market transformation efforts.
Keywords: Business Law